Multi-omics analyses demonstrate characteristics of changes in immune microenvironment during skin aging - Xiaojuan TENG; Jingxia LIN; Yongjun ZHANG; Xinquan ZENG; Xuefei LI; Renliang HE; Jiajian ZHOU (Pifu-xingbing zhenliaoxue zazhi, 2022)
Objective To investigate the changes in transcriptome and immune microenvironment during human skin aging through integrative analysis of multi-omics. Methods We collected RNA-seq data from 699 human skin tissues in GTEx project. Then, we analyzed gene expression in young (20~39) and aged (60~90) group using RNA-seq datasets. CIBERSORT were used to calculate the immune infiltration of each sample and analyzed the dynamics of immune infiltration during skin aging. The dynamics of immune cell population in the aged and young skin were compared through integrative analysis of single-cell RNA-seq derived from 2 young and 3 old subjects using Seuate R package. In addition, we investigated the expression of immune-related genes in immune cells and non-immune cells of the skin. Results Distinct transcriptomic differences were observed between aged and young group in both non-sun-exposed and sun-exposed skin. The up-regulated genes in aged group were enriched in inflammatory pathway. Particularly, 49 inflammatory-related genes were gradually up-regulated during skin aging. Even though we didn′t observe the significant changes in immune cell infiltration between aged and young group, a heterogeneity of the immune cell infiltration was observed in aged group. Further, scRNA-seq analysis showed that CD4+/CD8+ T cells were reduced in the aged skin, indicating the declined adaptive immune ability in the aged skin. Interestingly, we found that some non-immune cell types expressed immune-related genes, suggesting that they may contribute to the increased inflammation in the aged skin. Conclusions The cutaneous microenvironment and transcriptome change with aging, with elevated expression of inflammation-related genes. In comparison to the young skin, the aged skin displays reductions in T cells and increased expression levels of inflammation-related genes in non-immune cells, indicating a crucial role of non-immune cells in skin aging.